LEGAL PROTECTION FOR PROSPECTIVE NEW SHAREHOLDERS FOR THE PLAN TO ACQUIRE THE BANKRUPT COMPANY PT SRITEX IN A STATE OF BANKRUPTCY - Serlika Aprita; Rio Adhitya; Evi Purnama Wati (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Company Limited is subject independent law.Regulation about company limited in a way general set up in Constitution Number 40 of 2007 Concerning Limited Liability Companies . Formation arrangement special regarding this Company because of For can protect interest holder shares and creditors , as well as other related parties as well as interest company That Alone specifically if company in condition bankrupt . Example case real investor losses due to bankruptcy is PT Sri Rejeki Isman Tbk , or more known as Sritex , one of the company textile the largest in Indonesia, in terms of official stop its operation on Saturday , March 1 , 2025. One of the effort rescue company that is do restructuring company through plan acquisition . Research This use method normative nature descriptive analytical . Prioritize secondary data that is strengthened with primary data, then analyzed in a way legal qualitative. Protection law to potential investors in plan acquisition company PT. Sritex can done through various ways , such as : (a) Arrange protection law for holder share minority ; (b) Regulate acquisition in Constitution Number 40 of 2007 concerning Limited Liability Companies ; and (c) Providing right to holder shares that are not agree plan acquisition For request company buy share with reasonable price , Protection law for investors also can done via : Require openness information , Prevent practice market manipulation , Crackdown firm perpetrator violation .